Optimalisasi Penggunaan QRIS melalui SPPT Elektronik di Bapenda Kota Bandung - Triaji, Ermi; Sumiati, Imas; Vaughan, Regan (BESIRU : Jurnal Pengabdian Masyarakat, 2024)
BAPENDA's efforts in increasing public awareness in paying the UN in collaboration with the community through the RW Creative Competition which was attended by a number of regions in the city of Bandung showed positive results. One of them is RW Gempol Sari who won first place in the RW Create competition "Socialization of UN Payments with QRIS" showing an increase in public awareness in paying the UN, although not yet fully utilizing QRIS in UN payments made. This program is used by the KARASA community to encourage the creativity of young people who are members of the community. The creations made include murals and bran.